2016
DOI: 10.1080/17429145.2016.1172128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated and insect herbivory on nitrogen and protein precipitable phenolic concentrations of two legumes

Abstract: Protein-precipitating polyphenolics (PPPs) serve as a plant defense against herbivory, increasing with stress. We studied how varying intensities of simulated and Melanoplus differentialis herbivory affected (1) PPP concentration; (2) protein bound by PPP (PB); and (3) N concentration of panicled tick-clover (Desmodium paniculatum; PTC) and sericea lespedeza (Lespedeza cuneata; SL) leaf regrowth. Leaves of PTC that were submitted to simulated herbivory had lesser (p ≤ .05 for all significant differences) PPP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…() found that SL CT concentrations did not have a clear response to defoliation, while Blackmon et al . () reported that insect herbivory decreased with plant maturity. In a field study looking at the effect of season progression in repeatedly harvested and accumulated SL herbage, Muir et al .…”
Section: Introductionmentioning
confidence: 98%
“…() found that SL CT concentrations did not have a clear response to defoliation, while Blackmon et al . () reported that insect herbivory decreased with plant maturity. In a field study looking at the effect of season progression in repeatedly harvested and accumulated SL herbage, Muir et al .…”
Section: Introductionmentioning
confidence: 98%
“…Tannins are group of plant polyphenols present in all vascular plants including leguminous plants, forages, flowers, fruits, grasses and leguminous trees (Blackmon et al, 2016). First time, the word tannins was used by Seguim to explain the compound present in various plants extracts that have feature of converting animal hides to leather (Elgailani & Ishak, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Tannins have both harmful and beneficial effects depending on their nature, concentration, animal species, animal health and feed composition (Figures 1a and 1b). Several studies have reported that tannin based forages have anti-bloat and anthelmintic characteristics which improve the quality of meat and milk products, fatty acids composition and ruminant antioxidant status (Blackmon et al, 2016). In addition, these tannins containing plants also contribute to inhibit the enteric methane emission (Anantasook et al, 2016;Gunun et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation